The role of hope in adjustment to acquired hearing loss. - Kent B; La Grow S (International Journal of Audiology, 2007)
This study investigated the relationship between individual and disability characteristics and adjustment to acquired hearing loss, and the role hope has in that relationship. A sample of 114 adults with sensorineural hearing loss who had accessed hearing therapy services participated in the study. The mean age of the participants was 67 years. A survey of individual and disability characteristics, hope and adjustment was conducted. Multiple regression analyses were applied to examine possible moderating and mediating models. The results indicate that the degree of loss was the only statistically significant individual and disability characteristic related to adjustment. The trait of hope was found to serve as a mechanism by which the degree of loss affects adjustment. Hearing loss affects hope which in turn affects adjustment. Hope was found to account for 45% of the relationship between the degree of loss and adjustment. Additionally, the study found that self-efficacy and personal meaning may influence hope and despair dimensions in different ways. Discussion centres on the implication of these findings for intervention strategies used in rehabilitation programmes for those with a significant hearing loss.